EXTH-12. RADIATION ENHANCES MELANOMA RESPONSE TO IMMUNOTHERAPY AND SYNERGIZES WITH BENZODIAZEPINES TO PROMOTE ANTI-TUMOR ACTIVITY. (11th November 2019) - Pomeranz Krummel, Daniel; Nasti, Tahseen; Izar, Benjamin; Xu, Maxwell; Lowder, Lindsey; Press, Robert; Kaluzova, Milota; Kallay, Laura; Rupji, Manali; Burnham, Andre; Li, Guanguan; Ahmed, Taukir; et al.
Abstract: Melanoma brain metastases (MBM) occur in 50% of advanced melanoma patients. It is unclear if systemic therapies synergize with radiotherapy (RT) and what the impact of RT timing has on efficacy. We find that RT followed by ICI (immune checkpoint inhibitors) (RTàICI) improves MBM patient survival compared to other combination strategies, also shown here in a murine melanoma model. RNA-seq of MBM tumors in the RTàICI group exhibit overrepresentation of genes implicated in NFKB signaling. There is also expression of GABAA receptor subunits across both treatment groups. We show that melanoma cells express functional GABAA receptors and that benzodiazepines impair tumor growth. Combination of sub-lethal RT doses with benzodiazepine results in significant ipsilateral and out of field abscopal anti-tumor activity, which is associated with enhanced tumor infiltration with poly-functional CD8 T-cells. This study provides evidence that RT enhances MBM response to ICI and synergizes with benzodiazepines to promote anti-tumor activity.